Sex-Determining Region Y Chromosome-Related High-Mobility-Group Box 10 in Cancer: A Potential Therapeutic Target - Yu, Liming; Peng, Fan; Dong, Xue; Chen, Ying; Sun, Dongdong; Jiang, Shuai; Deng, Chao (Frontiers in Cell and Developmental Biology, 2020)
Sex-determining region Y-related high mobility group-box 10 (SOX10), a member of the SOX family, has recently been highlighted as an important essential transcriptional factor involved in developmental biology. Recently, the functionality of SOX 10 has been increasingly revealed by researchers worldwide. It has been reported that SOX10 significantly regulates the proliferation, migration, and apoptosis of tumors and is closely associated with the progression of cancer. In this review, we first introduce the basic background of the SOX family and SOX10 and then discuss the pathophysiological roles of SOX10 in cancer. Besides, we enumerate the application of SOX10 in the pathological diagnosis and therapeutic potential of cancer. Eventually, we summarize the potential directions and perspectives of SOX10 in neoplastic theranostics. The information compiled herein may assist in additional studies and increase the potential of SOX10 as a therapeutic target for cancer.